Explorations into Becoming New, Radical, and Quite Possibly Dangerously Progressive within an Aotearoa New Zealand Context - Nicola Dunham; Hazel Owen; Yo Heta-Lensen (MDPI AG, 2015)
This paper draws on an initiative where we experienced being new, radical, and, from some viewpoints, dangerously progressive at Unitec-a Polytechnic/Institute of Technology in Aotearoa, New Zealand. The initiative was driven by a need to improve student experiences of interdisciplinary learning and teaching, and to develop a common semester for students transitioning to a bachelor degree programme, as well as a new suite of interdisciplinary qualifications at postgraduate level. This discussion paper is situated within a self-study paradigm befitting educational contexts, by drawing on the reflective narratives of three participants who held a range of different roles-and, hence, perspectives within the change process. Interpretations and implications are discussed using the lens of the Inclusive Framework, to illustrate personal, professional, and political elements. Our overall aim is to add to current understandings of change within the higher education sector. However, this is a study of our own experiences and we are not making claims that we are in the possession of "truth", but, rather, we seek to identify aspects that may have relevance in other contexts. We conclude that navigating the next phase of transformative change in our context will involve seeking resolutions to key emerging questions. This includes exploring notions of multiple innovators, creating agile development environments in education and exploring the concept of time as multifaceted.